Prediction of temperature of standard fire exposure - Jefimovas, Andrejus; Mačiulaitis, Romualdas; Sikarskas, Donatas (Journal of Civil Engineering and Management, 2017)
This article describes equations derived to predict the duration of local pyrolytic charring under standard fire conditions. The equations consist of five variables: electrical capacity, electrical conductivity, calorific value, depth and rate of char. The equations are split up into two groups: one for the formation of non-impregnated carbonaceous residue, and one for impregnated carbonaceous residue during pyrolysis. This means that before predicting the local duration of charring, it is necessary to determine whether the wood has been impregnated with a fire retardant solution before the fire. Electrical conductivity and electrical capacity measurement methods were used for this purpose. The temperature of standard fire local exposure is calculated by predicting the duration of local pyrolytic charring according to the standard temperature and the time dependence of fire.